Reducing the effect of wave dispersion in a timber pole based on transversely isotropic material modelling. (15th January 2016) - Subhani, Mahbube; Li, Jianchun; Samali, Bijan; Crews, Keith
Highlights: Wave propagation in timber pole is solved considering it as anisotropic material. An experimental set up is proposed for the condition assessment of timber pole. Dispersion is more while considering timber as an anisotropic material. Reducing the effect of wave dispersion in utility timber pole is discussed. Abstract: Round timbers are used for telecommunication and power distribution networks, jetties, piles, short span bridges etc. To assess the condition of these cylindrical shape timber structures, bulk and elementary wave theory are usually used. Even though guided wave can represents the actual wave behaviour, a great deal complexity exists to model stress wave propagation within an orthotropic media, such as timber. In this paper, timber is modelled as transversely isotropic material without compromising the accuracy to a great extent. Dispersion curves and mode shapes are used to propose an experimental set up in terms of the input frequency and bandwidth of the signal, the orientation of the sensor and the distance between the sensors in order to reduce the effect of the dispersion in the output signal. Some example based on the simulated signal is also discussed to evaluate the proposed experimental set up.